Qualidade das informações contábeis e o ambiente regulatório: evidências empíricas no período de 1999 a 2013 - Vagner Antonio Marques (2016)
The financial information included as one of the sources of information to external users, allowing them, among others, to estimate the future value of the firm. To this end, they must have intrinsic qualitative characteristics that enhance or undermine its quality (MACKENZIE et al., 2013). In the last years there was a global effort to improve the quality of financial information culminating in Brazil, the adoption of the Standard IFRS - International Financial Reporting Standards (DECHOW & SCHRAND, 2004). It is that accounting serves as a mechanism of control and governance, but it could be used as a tool of manipulation of information (MECKLING & JENSEN, 1976; WATTS, 1992). In addition, several cases, such as Enron, have put in evidence the practical effects of the nature of individuals and fragility of mitigation mechanisms of agency conflicts (DI PIETRA, McLeay and Ronen, 2014). Finally, the adoption of IFRS has puzzled researchers, the accounting profession, users and standard-setters in accounting as to its real effects, as there are doubts about the effective improvement of the quality of financial information after the adoption of this standard (Ball, 2006). In this context, this thesis was to examine the effect of the regulatory environment on the quality of financial information as from five major proxies quality of accounting information, namely (DECHOW, GE and Schrand, 2010): (1) Restatement (2) Conservatism (3) Earings Persistence (4) Value Relevance and (5) Earnings Management. Specifically he studied how the adoption of SOX - Sarbanes-Oxley and IFRS affected the quality of proxies of accounting information mentioned above. a quality index information (IQIF) calculated from the quality of accounting information proxies addition was proposed. The descriptive, documental and quantitative approach study analyzed data from 344 companies traded on the BM e FBovespa from 1998 to 2013. Data were collected on the websites of the CVM - Brazilian Securities Commission and BM e FBovespa. As a data analysis strategy used the regression analysis with panel data, difference test between the average (median) and Cluster Analysis. The results showed that there was a substantial improvement on the quality of accounting information between the studied proxies, except for the restatements that showed an average growth over the period, but with a tendency of improvement after the adoption of full IFRS. The relevance and Earnings Persistence there was improvement in both the explanatory power (R²) and the significance of the do LPAit e do EBITit-1. With regard to Conservatism, there was an increase of Conservatism, except in the convergence period (2005-2007), however, a trend reversal loss was found in subsequent periods which was confirmed in the results management measure (GR). The Accruals Discretionary (AD) showed greater homogeneity, suggesting less variability in GR level, this homogeneity was verified by analysis of variance comparing the pre- and post-IFRS periods, but comparing the average between periods there was no difference statistically significant. Also it has been found that the SOX adoption year had a positive effect on the IQIF suggesting deterioration in the quality of financial information. On the other hand, the adoption of IFRS has reduced the IQIF showing improvement in the quality of financial information.